2019
DOI: 10.1093/advances/nmy119
|View full text |Cite
|
Sign up to set email alerts
|

Milk and Dairy Product Consumption and Bladder Cancer Risk: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Some studies have reported that milk and dairy product consumption reduces bladder cancer incidence, whereas others have reported null or opposite findings. This meta-analysis of 26 cohort and case-control studies has been conducted to pool the risk of the association between milk and dairy products and bladder cancer. A systematic search in MEDLINE, EMBASE, and the Web of Science (from inception to 30 April 2018) was conducted. Random-effects models were used to compute pooled estimates of RR for high or medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 65 publications
2
28
0
2
Order By: Relevance
“…BCAC Breast Cancer Association Consortium, CI confidence interval, OR odds ratio, PRACTICAL Prostate Cancer Association Group to Investigate Cancer Associated Alterations in the Genome consortium a lower risk of bladder and breast cancer or with a higher risk of prostate cancer, though a positive association between genetically predicted milk consumption and prostate cancer was found in the FinnGen consortium. For bladder cancer, observational studies have reported a protective association mainly with the consumption of fermented milk products (cultured milk, yogurt, and cheese) [12,30]. The lactase persistence variant is not associated with yogurt and cheese consumption [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…BCAC Breast Cancer Association Consortium, CI confidence interval, OR odds ratio, PRACTICAL Prostate Cancer Association Group to Investigate Cancer Associated Alterations in the Genome consortium a lower risk of bladder and breast cancer or with a higher risk of prostate cancer, though a positive association between genetically predicted milk consumption and prostate cancer was found in the FinnGen consortium. For bladder cancer, observational studies have reported a protective association mainly with the consumption of fermented milk products (cultured milk, yogurt, and cheese) [12,30]. The lactase persistence variant is not associated with yogurt and cheese consumption [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis from Bermejo et al (36) pooled the results of 26 cohort and case-control studies to determine the association between milk and dairy products and bladder cancer. Overall, medium compared with low consumption of total dairy products, milk, and fermented dairy products was significantly associated with lower pooled risk for bladder cancer.…”
mentioning
confidence: 99%
“…An updated WCRF-AICR Continuous Update Project in 2017 indicated that colorectal cancer risk decreased by 13% for each 400 g/day increment of dairy product consumption (95% CI: 10-17%) (17). Similarly, four recent meta-analyses (8,11,18,19) reported an inverse association between intake of dairy products, especially fermented dairy foods and bladder cancer risk. These associations may differ by geographical region.…”
Section: Discussionmentioning
confidence: 99%
“…However, the two prospective studies ( 9 , 10 ) included in this meta-analysis have reported inconsistent results. Another meta-analysis by Bermejo et al ( 11 ) also indicated a reduced risk of bladder cancer associated with medium consumption of total dairy products and with medium and high consumption of milk and fermented dairy products. However, a pooled analysis of 13 cohort studies by Acham et al ( 12 ) failed to find a significant association between total or individual dairy products and bladder cancer risk.…”
Section: Introductionmentioning
confidence: 93%